Аналіз методології та методик науково-педагогічних досліджень - Мамонько, Д. В. (ХНУРЕ, 2020)
This article is devoted to the problems of analysis of methodology and methodology is conducted in the work scientific and pedagogical research. The theoretical and practices methods are analyses. Especially attention is devoted to the pedagogical methods of decision
Keywords: філософія; науково-педагогічні дослідження